Bitter taste receptors in the domestic dog (Canis familiaris) - Gibbs, Matthew (2021)
The sense of taste, or gustation, combines with olfactory and somatosensory cues to give the overall perception of flavour once a food is accepted into the mouth. The perception of bitter taste is thought to be primarily associated with rejection of a food, and protects animals from ingesting potentially toxic substances. Bitter taste is mediated through a group of G protein-coupled receptors known as the Taste type 2 receptors (Tas2rs) that are expressed in taste papillae on the tongue, and other surfaces in the oral cavity.